Associação de enzimas amilase e xilanase sobre o desempenho e saúde intestinal de frangos de corte - Colcetta, Bárbara (2023)
This work aimed to evaluate the association of amylase and xylanase enzymes in broiler chicken diets during the grower phase on performance, intestinal morphometry and histopathology, short-chain fatty acid profile of cecal content, serum cytokine concentration and economic analysis of production. In the experiment, a total of 980 one-day-old male Cobb 500® broiler chicks were distributed in a completely randomized design, in a 2 x 3 + 1 factorial scheme, with two levels of amylase (100 and 200 U kg-1) x three levels of xylanase (0,1000 and 2000 U kg-1) + one positive control (PC), totaling seven treatments, with seven replications of 20 birds per experimental unit. The PC was formulated according to the nutritional requirements of the lineage. The diets containing amylase and xylanase had the nutriotinal matrix valued at 100 kcal of metabolizable energy and 6% of crude protein and digestible amino acids (lysine, methionine, methionine + cystine, threonine and tryptophan). At 14 days, birds that consumed 1000 U kg-1 of xylanase had better feed conversion compared to birds that did not receive diets containing enzymes, while with enzymatic supplementation feed intake and weight gain was similar to PC. Diets containing 100 U kg-1 of amylase, without xylanase, provided better I See Inside (ISI) score indices. No difference was found for the morphometric parameters, in the concentration of acetic, butyric and isovaletic acids and in the concentration of interleukins 6, 10 and 16 of the chickens at 28 days of age. The analysis of the feed cost showed that enzymatic supplementation, both amylase and xylanase, is economically viable, reducing approximately 3.3% the production cost in relation to PC. The performance of broilers that received amylase and xylanase with reduced energy and protein did not match the group that received diets without inclusion of enzymes and higher nutritional levels and did not affect the intestinal health and immunological parameters of the birds at 28 days of age. Considering the economic viability analysis, the enzyme supplementation provided a reduction in the feed cost of production of broiler chickens up to 28 days of age.